Egalitarian-Equivalent Cost Sharing of a Public Good - Moulin, Herve (Econometrica, 1987)
In an economy with one public and one private good, egalitarian-equivalent cost sharing consists of finding the highest public good level, x*, such that consuming x* for free yields a feasible utility distribution. The corresponding feasible allocation (typically unique), called egalitarian-equivalent, is in the core of the economy. Conversely, any cost sharing method satisfying Pareto optimality, cost monotonicity (nobody suffers a utility loss if the production technology improves upon, ceteris paribus), and individual rationality (no single-agent coalition objects) or no private transfers (no agent receives a positive amount of private good), must select an egalitarian-equivalent allocation in every economy. Copyright 1987 by The Econometric Society.